Exploring the pharmacokinetics and tolerability of cyclooxygenase inhibitor ampiroxicam: a phase I study on single and multiple oral doses - Zhao, Pengfei; Qi, Ying (Frontiers in Pharmacology, 2024)
Ampiroxicam is a long-acting, non-steroidal anti-inflammatory drug that selectively targets human cyclooxygenase to effectively alleviate fever, pain, and inflammation. This study aimed to assess its tolerability and pharmacokinetics and lay the groundwork for personalized dosing through experiments conducted on healthy participants. Pharmacokinetic experiments in healthy individuals quantified the presence of the ampiroxicam metabolite piroxicam in plasma using ultra-performance liquid chromatography. Piroxicam was selected as a marker because of its role in the ampiroxicam metabolic pathway. Importantly, the presence of endogenous substances in the plasma did not cause interference.This method was validated to ensure its accuracy and precision. This study involved both single-(low, medium, and high levels) and multiple-dose administration of ampiroxicam in healthy subjects. Pharmacokinetic parameters were determined. A clear dose-dependent increase was observed in AUC0-216, AUC0-∞ , and Cmax. Notably, there were no significant differences among the various dosage groups.Sex-specific distinctions were insignificant, except for MRT in the multiple-dose group, which was potentially influenced by variations in body weight. The study demonstrated the safety and efficacy of ampiroxicam in different dosage regimens, providing a solid basis for its application in clinical settings and highlighting its potential for personalized medicine approaches in pain and inflammation management.